Beverage Branding and Social Dynamics: A Critical Discourse Analysis of Soft Drink Slogan - Ahmed Srosh, Mursaleen (JELLL, 2025)
This study looks at how soft drink slogans affect both branding and social trends. Using Fairclough's three-part model, we examine the language, cultural meanings, and hidden messages in slogans from four big soft drink companies. We find that these slogans are not just for advertising, but also act as mirrors of society's values, identities, and power dynamics. By analyzing the words used in these slogans, we uncover how brands try to connect with people's feelings, dreams, and sense of self. We also see how slogans can support or question social beliefs about health, lifestyle, and consumer habits. Our research helps us better understand how language, branding, and social trends interact in the beverage industry. This work is useful for marketers, language experts, and social scientists who are interested in how brands communicate and influence people and society.